극후판 다층 FCAW 맞대기 용접부의 잔류응력 특성에 관한 연구 - 방희선(Hee-Seon Bang); 방한서(Han-Sur Bang); 이윤기(Yoon-Ki Lee); 김현수(Hyun-Su Kim); 이광진(Kwang-Jin Lee) (Han-guk haeyang gonghak hoeji (Online), 2010)
The goal of this work is to establish the reliability of FCA welded joints for high strength EH36-TMCP ultra thick plate. For this, heat conduction and thermo elasto-plastic analyses have been conducted on a multi-pass, X-groove, butt-joint model to clarify the thermal and mechanical behavior (residual stresses, magnitude of the stresses, and their production and distribution mechanisms) of the weld joint. In addition, the results of the welding residual stress obtained from thermo elasto-plastic analysis was verified and compared with results obtained by XRD analysis.